Answer:
[tex]y = 8.4547x - 11.9396[/tex]
Step-by-step explanation:
We are given the following information in the question:
[tex]y = (x^2-x)ln(6x)[/tex]
Differentiating y with respect to x:
[tex]\displaystyle\frac{dy}{dx} = (x^2-x)'ln(6x) + (x^2-x)(ln(6x))'\\=(2x-1)ln(6x) + (x^2-x)\frac{6}{6x}\\\\= (2x-1)ln(6x) + (x-1)[/tex]
At x =2
[tex]\displayatyle\frac{dy}{dx}\Bigr|_{\substack{x=2} }= (4-1)ln(12) + (2-1) = 8.4547[/tex]
[tex]y(2) = (2^2-2)ln(12) = 4.9698[/tex]
Equation of tangent:
[tex](y-y_0) = \displaystyle\frac{dy}{dx}(x-x_0)[/tex]
Putting the values:
[tex](y-y(2)) = \displaystyle\frac{dy}{dx}\Bigr|_{\substack{x=2} }(x-2)\\\\y - 4.9698 = 8.4547(x-2)\\y - 4.9698 = 8.4547x - 16.9094\\y = 8.4547x - 11.9396[/tex]
The above equation is the required equation of the tangent.